Enhanced photocatalytic degradation of methylene blue by nanocomposites prepared by laser ablation of Bi on CNT-α-Fe2O3 nanoparticles. (November 2022) - Manda, Abdullah A.; Elsayed, Khaled A.; Gaya, Umar Ibrahim; Haladu, Shamsuddeen A.; Ercan, İsmail and Ercan, Filiz and Alheshibri, Muidh and Al Baroot, Abbad and Kayed, T.S. and Alshammery, Sultanah and Altamimi, Nafala A. and Al-Otaibi, Amal L.
Highlights: Synthesis of Bi@CNT-α-Fe2 O3 nanocomposite by laser ablation in liquid. Optical, morphological, and crystallographic characterizations of the nanocomposites. Enhanced photocatalytic degradation of methylene blue by Bi@CNT-α-Fe2 O3 nanocomposites prepared by laser ablation. Complete degradation of MB occurred in 20 min. Abstract: The low conductivity and high combination rate of photogenerated electrons (e-) and photogenerated holes (h+) are the real challenges of photocatalysis. These problems could be mitigated by the synthesis of heterostructured nanocomposites (NCs). In this study, Bi@CNT-Fe2 O3 nanocomposite was fabricated via pulsed laser ablation in liquid and characterized by UV–Vis spectroscopy, photoluminescence (PL), X-ray diffraction (PXRD) and field scanning electron microscopy (FESEM). These techniques revealed successfully the formation of CNT-α-Fe2 O3 and Bi@CNT-α-Fe2 O3 nanocomposites. The photocatalytic activities of the Fe2 O3, CNT-α-Fe2 O3, and Bi@CNT-Fe2 O3 photocatalysts were evaluated by the degradation of methylene blue (MB) dye under ultraviolet (UV) light irradiation in the presence of a very low concentration of hydrogen peroxide (H2 O2 ) as an oxidizing agent. The results show that the Bi@CNT-α-Fe2 O3 NC has the highest photocatalytic degradation efficiency of MB which completes in 20 min of UV light irradiation. In addition, the obtained rate constants (min −1 ) of Bi@CNT-α-Fe2 O3 NC were 1.3 and 3.4 times higher than those of CNT-α-Fe2 O3 and α-Fe2 O3. nanocatalysts, respectively.